Promyelocytic leukemia protein promotes the phenotypic switch of smooth muscle cells in atherosclerotic plaques of human coronary arteries. Issue 7 (16th April 2021) - Karle, Weronika; Becker, Samuel; Stenzel, Philipp; Knosalla, Christoph; Siegel, Günter; Baum, Oliver; Zakrzewicz, Andreas; Berkholz, Janine
Abstract: Promyelocytic leukemia protein (PML) is a constitutive component of PML nuclear bodies (PML-NBs), which function as stress-regulated SUMOylation factories. Since PML can also act as a regulator of the inflammatory and fibroproliferative responses characteristic of atherosclerosis, we investigated whether PML is implicated in this disease. Immunoblotting, ELISA and immunohistochemistry showed a stronger expression of PML in segments of human atherosclerotic coronary arteries and sections compared with non-atherosclerotic ones. In particular, PML was concentrated in PML-NBs from α-smooth muscle actin (α-SMA)-immunoreactive cells in plaque areas. To identify possible functional consequences of PML-accumulation in this cell type, differentiated human coronary artery smooth muscle cells (dHCASMCs) were transfected with a vector containing the intact PML-gene. These PML-transfected dHCASMCs showed higher levels of small ubiquitin-like modifier (SUMO)-1-dependent SUMOylated proteins, but lower levels of markers for smooth muscle cell (SMC) differentiation and revealed more proliferation and migration activities than dHCASMCs transfected with the vector lacking a specific gene insert or with the vector containing a mutated PML-gene coding for a PML-form without SUMOylation activity. When dHCASMCs were incubated with different cytokines, higher PML-levels were observed only after interferon γ (IFN-γ) stimulation, while the expression of differentiation markers was lower. However, these phenotypic changes were not observed in dHCASMCs treated with small interfering RNA (siRNA) suppressing PML-expression prior to IFN-γ stimulation. Taken together, our results imply that PML is a previously unknown functional factor in the molecular cascades associated with the pathogenesis of atherosclerosis and is positioned in vascular SMCs (VSMCs) between upstream IFN-γ activation and downstream SUMOylation.